The Legal Qualification of the Marriage Mediation Contract - Hassan, Wafaa; Hassan, Haider (Journal of Legal Sciences, 2023)
Although the profession of a marriage mediator is dominated by a social character, and it is also characterized by its practice in the midst of strict secrecy, because Eastern societies innately reject this method of searching for a life partner. The two parties play a prominent role of the will in the events of legal effects, and the obligations and rights owed by the contracting parties, which leads us to consider the agreement between the mediator and the one who wants to marry going to the purely contractual nature, and thus requires the correct legal adaptation on the contractual relationship that is achieved between the marriage mediator and his clients from Those who want to get married and therefore we will divide this research into six demands to clarify the legal qualification of the marriage mediation contract.